Overweight and Obesity Among Chinese College Students: An Exploration of Gender as Related to External Environmental Influences - Jiang, Shuhan (Am J Mens Health, 2018)
While many studies have examined factors associated with overweight and obesity among college students, no study has yet compared gender differences influencing overweight and obesity using a multilevel framework. The present study examines different influences on overweight and obesity between men and women at both individual and environmental levels. Participants were 11,673 college students identified through a multistage survey sampling process conducted in 50 Chinese universities. The prevalence of overweight and obesity was 9.5% (95% CI [7.7, 11.3]) in the overall study sample, 13.9% (95% CI [11.5, 16.7]) in males and 6.1% (95% CI [4.1, 8.1]) in females, respectively. We found that higher family income, perceived life stress, home region GDP, and university city unemployment were associated with higher overweight and obesity levels in males, independent of other individual- and city-level covariates. However, unlike male students, only unemployment was associated with overweight and obesity among females. Our research indicates Chinese males are more susceptible to overweight and obesity, and are more easily influenced by external variants than Chinese females. This information should be considered in formulating gender-specific policies and designing and implementing effective interventions to reduce the prevalence of overweight and obesity among young adult male college students.